Popliteal aneurysms: surgical treatment - Rubio, Roberto; Abo, Juan C; Sanjines, Aníbal; Zerbino, Víctor (Cirugía del Uruguay, 2020)
Two cases of complicated popliteal arterial aneurysms are presented. The first corresponds to a 80 years old man in severe congestive heart failure, showing a left popliteal aneurysms with good collateral arterial circulation to the distal portion of the limb.